1966
DOI: 10.1039/j39660001245
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic amidines. Part XX. Polyaza- and oxapolyaza-benzonaphthanthracenes

Abstract: Polyaza-and oxapolyaza-benzonaphthanthracenes, isosteric with tricycloquinazoline, have been synthesised.Various eliminations from appropriately substituted arylpolyazabenzanthracenes readily gave these hexacyclic compounds. The oxadiaza analogue is intensely carcinogenic. Correlation of their activities with previously described isomers and isosteres shows the critical significance of certain symmetry factors for activity. THE carcinogen, tricycloquinazoline (I) has a unique trigonal symmetry; loss of symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the course of their investigations on tricycloquinazoline and its carcinogenic properties, published mostly in the 1960s, Partridge and co-workers synthesized a number of related cyclic amidine derivatives, including isomers of 139.1 ( 140.7 , 140.9 , and 140.15 ), triaza systems ( 140.12 , 140.13 , 140.17 , 140.19 ), and diazaoxa systems 140.3 , and 140.22 , (Scheme ). The synthetic strategies mostly relied on classical dehydrative condensations and nucleophilic substitutions, and were generally concise and high-yielding.…”
Section: Phenalenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of their investigations on tricycloquinazoline and its carcinogenic properties, published mostly in the 1960s, Partridge and co-workers synthesized a number of related cyclic amidine derivatives, including isomers of 139.1 ( 140.7 , 140.9 , and 140.15 ), triaza systems ( 140.12 , 140.13 , 140.17 , 140.19 ), and diazaoxa systems 140.3 , and 140.22 , (Scheme ). The synthetic strategies mostly relied on classical dehydrative condensations and nucleophilic substitutions, and were generally concise and high-yielding.…”
Section: Phenalenoidsmentioning
confidence: 99%
“… a Reagents and conditions: (a) AcOH, 180–190 °C, 90 min; (b) (1) acetone, 30 min, (2) NH 3 /EtOH; (c) neat, 210 °C, 1 h; (d) (1) NaCl, AlCl 3 , 100–320 °C, 1 h, (2) NaNO 3 , HNO 3 (76% as nitrate), (3) NEt 3 ; (e) (1) POCl 3 , PCl 5 , 120–140 °C, 3 h, (2) 2-aminopyridine; (f) NaCl, AlCl 3 , 320 °C, 1 h; (g) neat, 320 °C, 15 min; (h) N 2 H 4 , Raney Ni, EtOH, 70 °C; (i) aniline, reflux, 30 min; (j) DMF, aq NaOH, reflux, 15 min; (k) H 2 , Pd/C, EtOH. …”
Section: Phenalenoidsmentioning
confidence: 99%
“…The formation of phenoxathiins (e.g., 295, 297) by the reaction of o-chloronitroarenes (293) with o-mercaptophenol (294) and its derivatives (296) was first reported by Mauth-nersi9,320 an(j later by Poliak and Riesz.321•322 However, no attempt was made to establish the orientation of the phenoxathiin products. The problem of orientation was clarified by Stevenson and Smiles323 who demonstrated that the intramolecular displacement of the nitro group implicit in these reactions is effected by the hydroxy rather than the thiol group (cf.…”
Section: N H20-pyridine Heatmentioning
confidence: 99%
“…The same triazaphenalene had previously been reported by Moszew by oxidation of alleged 7-anilino-6-phenyl-5,12-diazabenz[a]anthracene (5). However the compound (2) prepared by the unequivocal method of Partridge ' melted at 317 "C whereas Moszew reported a melting point of 245 "C and, more importantly, antitumour properties.' In the light of this atypical activity in a series of compounds noted for their frequent and often intense mutagenic and carcinogenic properties6 it was decided to reinvestigate the reaction and establish the structure of Moszew's product.…”
Section: School Of Pharmacy and Pharmacology University Of Bath Bath ...mentioning
confidence: 99%